Kajian Ketersediaan Pupuk Bersubsidi Terhadap Kebutuhan Bertanam Padi Dalam Rangka Mewujudkan Ketahanan Pangan di Kabupaten Deli Serdang - Resmiwati Isnaini; Rahmanta Ginting; Yusniar Lubis (Universitas Medan Area, 2018)
ABSTRACTPaddy is a food ingredient that produces rice which is the staple food lndonesian population that are not easily replaced by other feed ingredients. Rice is a social commodity therefore changes in rice would be so easy mepengaruhi other social and economic life. Therefore the government's attention to rice supply be a program priorities. The research objectives are: 1). to assess the availability of subsidized fertilizer to rice cultivation needs in order to achieve food security at Deli Serdang Regency, 2) to assess the fertilizer subsidy will increase the rice productivity at Deli Serdang Regency, 3) to assess the fertilizer subsidy will increase rice production in Deli Serdang Regency .The results of this study shows that : 1) the provision of fertilizer subsidies for Deli Serdang Regency is very supportive of the needs of rice cultivation in order to achieve food security at Deli Serdang Regency, 2) the fertilizer subsidy for the Deli Serdang Regency had been increased the land productivity per hectare, 3) the fertilizer subsidy for the Deli Serdang Regency had been increased the rice production at Deli Serdang Regency. The availability of subsidized fertilizer to food security will increase the productivity of land and increase the production of rice based on the SWOT analysis, then the realization of food security in Deli Serdang Regency. Keywords: availability of fertilizer subsidies, food security, SWOT